ISTRI KARIER DALAM MEWUJUDKAN KELUARGA SAKINAH - Emy Ria Wahyu; Ibnu Jazari; Dwi Ari Kurniawati (Jurnal Hikmatina, 2020)
AbstractIslam does not prohibit a wife from working outside the house, but must still pay attention to the things established by Islam and obtain permission from the husband. If a husband permits his wife to work outdoors, it means that there must be a commitment to help each other in the household chores and educate the child. To create a family of Sakinah in a career wife's household, must perpedomandengan the things that have been in the Qur'an and Hadist. It should also be based on the attitude of honesty, openness, and mutual trust. The purpose of the study was to know how to create a harmonious family and a sacnication in a career women's household in the Brigif dormitory of the 18th Jabung Raider. The methood  used is qualitative whereas the tipe of research that is the casse study in the Brigif dorm of the Raider 18 Jabun. To collect research data using observation, documentation, and interviews, then analyse it with data triangulation. A lot of things are a contributing factor to a career woman. In general, there are two factors that encourage women to pursue a career, namely the desire factor and the demands factor. Economic factors, social factors, education level. Keyword: Peaceful family, household, career woman.